Perancangan Struktur Metode Student Centre Learning (SCL) Dalam Mata Kuliah Sistem Akuntansi Dengan Kurikulum Berbasis Kompetensi (KBK) - Zahara; Afni, Zalida (Akuntansi dan Manajemen, 2015)
This research porpuse to design the structure of Student Centre Learning (SCL) methode in accounting system subject that use curriculum based on competency. This is an action research in accounting system study at accounting departement of Padang State Polytechnic. This research uses Kemmis dan Mac Tanggart model which is devided in 5 steps that are: 1. Planning, 2. Action&Observation, 3. Reflecting&Replanning, 4. Action&Observation and 5. Reflecting. The application of SCL metode in accounting system study will be evaluated based on the score of studying observation, student respons and student score academic in accounting system. The observation and student respons questioners are measured by Linkert scale for 5 level as well as student academic score there are: 5=A=Very Good, 4=B=Good, 3=C=Enought, 2=D=Bad, and 1=E=Very Bad. All of score data will be process by SPSS package program to define the appropriateness of SCL methode for accounting system subject. This research is still going on to the second step. There are 5 SCL model that chosen as the result of the first step research (planning) i.e. Small Group Discussion, Discovery Learning, Role Play, Contextual Instruction dan Problem Based Learning.